Integrated Solution in an Office Room with Diffuse Ceiling Ventilation and Thermally Activated Building Constructions. (November 2015) - Zhang, Chen; Heiselberg, Per Kvols; Pomianowski, Michal; Yu, Tao; Jensen, Rasmus Lund
Abstract: An integrated system is proposed in this study to combine diffuse ceiling ventilation with a thermally activated building construction (TABS), aiming to provide cooling/ heating and ventilation to an office room all year around. The performance of the integrated system is evaluated by full-scale experiments in a climate chamber. The experimental results indicate that diffuse ceiling can significantly improve thermal comfort in the occupied zone, by reducing draught risk and vertical temperature gradient. The linear function between pressure drop and air change rate points out that the air flow through diffuse ceiling is laminar. A thermal decay is found in the plenum air and the thermal performance of TABS may be influenced by water flow and air flow direction.